Antibacterial activity of leaves extracts of Trifolium alexandrinum Linn. against pathogenic bacteria causing tropical diseases - Khan, Abdul Viqar; Ahmed, Qamar Uddin; Shukla, Indu; Khan,, Athar Ali (Elsevier, 2012)
Objective: To investigate antibacterial potential of Trifolium alexandrinum Linn. (Fabaceae, Egyptian clover) against seven G+ve and eleven G– ve hospitals isolated human pathogenic bacterial strains responsible for many tropical diseases. Methods: Non-polar and polar extracts of the leaves of T. alexandrinum i.e., hexane, dichloromethane (DCM), ethyl acetate (EtOAc), methanol (MeOH) and aqueous (AQ) extracts at five different concentrations (1, 2, 5, 10 and 15 mg/ml) were prepared to evaluate their antibacterial value. NCCL standards were strictly followed to perform antimicrobial disc susceptibility test using disc diffusion method. Results: Polar extracts demonstrated significant antibacterial activity against tested pathogens. EtOAc and MeOH extracts showed maximum antibacterial activity with higher inhibition zone and were found effective against seventeen of the tested pathogens. While AQ plant extract inhibited the growth of sixteen of the test strains. EtOAc and MeOH plant extracts inhibited the growth of all seven G+ve and ten of the G-ve bacterial strains. Conclusion: Present study strongly confirms the effectiveness of crude leaves extracts against tested human pathogenic bacterial strains causing several tropical diseases. Since Egyptian clover is used as a fodder plant, it could be helpful in controlling various infectious diseases associated with cattle’s as well.